Evaluación de la factibilidad técnico-financiera para el proceso de extracción de b-caroteno partiendo de desechos de zanahoria variedad Chantenay (Daucus carota L.) (2019)
The following dissertation was carried out with the aim of determining the feasibility of the B-carotene extraction process from Chantenay-variety carrot waste disposed by the company Hortalizas Boyacá S.A.S. using solid-liquid extraction techniques of bioactive compounds. A thorough investigation and comparison of previous studies related to the extraction techniques of carotenoids, specifically of B-carotene, was conducted, allowing to stablish the processing parameters and conditions such as temperature, time, solid-liquid ratio and extraction solvent. The selected parameters for the conventional Soxhlet extraction were: extraction temperature 70°C, extraction time 6h, solid-liquid ratio 2:10 and hexane as solvent. While for the ultrasound assisted extraction three temperature and time extraction conditions were selected (10, 20 and 30 min) and (30, 40 and 50°C) respectively, solid-liquid ratio 2:10 and sunflower oil was used as solvent.